PEMANFAATAN TUMBUHAN LIAR OLEH MASYARAKAT DESA SUCI DI JALUR PENDAKIAN AIR TERJUN TANCAK GUNUNG PASANG KABUPATEN JEMBER SERTA PEMANFAATANNYA SEBAGAI E-BOOKLET - Mariatul Kiptiah; Imaniah Bazlina Wardani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the utilization of wild plants by the community of Suci Village along the Tancak Waterfall hiking trail, Gunung Pasang, as a form of local wisdom that is still practiced but has not been systematically documented, making it vulnerable to gradual loss over time. This study aimed to identify wild plant species, describe their utilization based on use categories, Use Value (UV) and Plant Part Value (PPV), and determine the validity of an e-booklet as a learning resource. A descriptive qualitative approach was employed using observation, semi-structured interviews, documentation, and validation questionnaires for data collection. Data were analyzed using the Miles, Huberman, and Saldaña model, while ethnobotanical analysis applied the UV and PPV indices. The results revealed 32 wild plant species belonging to 23 families. These plants were utilized as food, traditional medicine, animal feed, ornamental plants, and handicraft materials. The highest Use Value was obtained by Leucaena leucocephala and Elephantopus scaber (1.6), while the Plant Part Value analysis indicated that leaves were the most frequently utilized plant part (40%). The developed e-booklet achieved an average validation score of 88.55%, indicating that it is highly valid and suitable for use as a learning resource.